Evaluasi Implementasi Peer Mentoring dalam Meningkatkan Kualitas Pembelajaran Guru di UPT SMP Negeri 4 Pringsewu - Nasib Suheri; Sofwan Adiputra; Arman; Siswoyo (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2026)
This study aims to evaluate the implementation of the peer mentoring program in improving the quality of teacher learning at the UPT SMP Negeri 4 Pringsewu. The peer mentoring program is seen as a continuous professional development strategy that emphasizes peer collaboration, reflection on learning practices, and sharing experiences among teachers. This study uses a qualitative approach with the CIPP (Context, Input, Process, Product) evaluation model to obtain a comprehensive picture of the program's suitability to school needs, resource readiness, implementation process, and program outcomes and sustainability. Data collection techniques include in-depth interviews, observations, and documentation studies involving the principal, mentor teachers, and peer mentoring participant teachers. Data analysis was conducted thematically through the stages of data reduction, data presentation, and conclusion drawing.The research results indicate that, contextually, the implementation of peer mentoring is relevant to the need to improve the quality of learning and strengthen a collaborative culture in schools. Based on these findings, the peer mentoring program was deemed effective and worthy of continuation with a strengthened monitoring system, more flexible scheduling, and ongoing school policy support. Keywords: Peer Mentoring, Learning Quality, Teacher Professional Development. Abstrak: Penelitian ini bertujuan untuk mengevaluasi implementasi program peer mentoring dalam meningkatkan kualitas pembelajaran guru di UPT SMP Negeri 4 Pringsewu. Program peer mentoring dipandang sebagai strategi pengembangan profesional berkelanjutan yang menekankan kolaborasi sejawat, refleksi praktik pembelajaran, dan saling berbagi pengalaman antarguru. Penelitian ini menggunakan pendekatan kualitatif dengan model evaluasi CIPP (Context, Input, Process, Product) untuk memperoleh gambaran komprehensif mengenai kesesuaian program dengan kebutuhan sekolah, kesiapan sumber daya, proses pelaksanaan, serta hasil dan keberlanjutan program. Teknik pengumpulan data meliputi wawancara mendalam, observasi, dan studi dokumentasi yang melibatkan kepala sekolah, guru mentor, dan guru peserta peer mentoring. Analisis data dilakukan secara tematik melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan.Hasil penelitian menunjukkan bahwa secara konteks, implementasi peer mentoring relevan dengan kebutuhan peningkatan kualitas pembelajaran dan penguatan budaya kolaboratif di sekolah. Berdasarkan temuan tersebut, program peer mentoring dinilai efektif dan layak untuk dilanjutkan dengan penguatan sistem monitoring, penjadwalan yang lebih fleksibel, serta dukungan kebijakan sekolah yang berkelanjutan. Kata Kunci: Peer Mentoring, Kualitas Pembelajaran, Pengembangan Profesional Guru.